ANALISIS KESALAHAN MAHASISWA PENDIDIKAN MATEMATIKA DALAM MENYELESAIKAN SOAL GEOMETRI PADA TOPIK BANGUN RUANG [ERROR ANALYSIS OF STUDENTS IN THE MATHEMATICS DEPARTMENT IN SOLVING GEOMETRY PROBLEMS ON THE TOPIC OF SOLID FIGURES] - Listiani, Tanti; Dirgantoro, Kurnia P. S.; Saragih, Melda J.; Tamba, Kimura Patar (Universitas Pelita Harapan, 2019)
Geometry is a branch of science in mathematics and a course taken by students of mathematics education. Based on students' final exam scores, results were not optimal with several types of errors detected. This study aimed at identify student mistakes in solving geometry problems on the topic of solid figures. The subjects of this study were mathematics education students in the even semester of the 2018/2019 academic year at Universitas Pelita Harapan in Tangerang. The type of research was a qualitative descriptive study. The data collection technique used was a test. The results showed that students' errors in solving geometry problems were concept errors, calculation errors, and a lack of accuracy because they were in a hurry.BAHASA INDONESIA ABSTRACT: Geometri merupakan salah satu cabang ilmu dalam matematika dan merupakan matakuliah yang wajib diikuti oleh mahasiswa program studi pendidikan matematika. Berdasarkan nilai ujian akhir semester mahasiswa didapatkan hasilnya masih kurang maksimal, hal ini memungkinkan terdapat beberapa tipe kesalahan jawaban dari mahasiswa. Penelitian ini bertujuan untuk mengidentifikasi kesalahan mahasiswa dalam menyelesaikan soal UAS geometri pada topik bangun ruang. Subjek penelitian ini adalah mahasiswa pendidikan matematika semester genap Universitas Pelita Harapan Tangerang tahun akademik 2018/2019. Jenis penelitian ini adalah penelitian deskriptif kualitatif. Teknik pengumpulan data yang digunakan adalah tes. Hasil penelitian menunjukkan bahwa kesalahan mahasiswa dalam menyelesaikan soal geometri adalah kesalahan konsep, kesalahan hitung, dan kurang teliti karena terburu-buru.